THE INTERACTION OF Co2+-AMMONIA MODELLING: THE COMPARATIVE STUDY BETWEEN AB INITIO AND ELECTRON CORRELATION METHODS - Harno Dwi Pranowo; Foliatini Foliatini; Karna Wijaya (Indonesian Journal of Chemistry, 2002)
Research on comparison between Hartree-Fock method and electron correlation methods as well as the effect of size of basis sets on representing interaction of Co2+-NH3 observed from complex energy parameters and optimum geometric parameters have been carried out.The first step is screening basis sets based on charge transfer effect and BSSE value. The selected basis set does not yield charge transfer at 1,4 Å <  < 8 Å, and yield small BSSE value. Electron correlation methods used are Møller-Plesset order 2 (MP2), Møller-Plesset order 3 (MP3), Configuration Interaction, Doubles (CID), dan Configuration Interaction, Singles and Doubles (CISD) whereas the basis set used is the result of the screening. LANL2DZ ECP-6-31G* and LANL2DZ ECP-6-311++G(3df,3pd)  basis sets are used with Unrestricted Hartree-Fock (UHF) and Møller-Plesset order 2 (MP2) methods to study the effect of size of basis sets.The result of the research showed that the best basis set is LANL2DZ ECP for Co2+ and 6-31G* for NH3. The application of electron correlation method and large basis set can increase the quality of interaction representation of Co2+- NH3. Møller-Plesset (MP) perturbation method gives larger contribution to correlation energy than Configuration Interaction (CI) method.